Squamous cell carcinoma arising within verrucous carcinoma of the oral cavity: a case report - Terada, Tadashi (e-Century Publishing Corporation, 2012)
The author herein reports a case of squamous cell carcinoma (SCC) arising within verrucous carcinoma (VC) of the hard palate. An 84-year-old woman was admitted to our hospital complaining of oral discomfort. Oral examination revealed a pedunculated verrucous tumor (15 x 15 mm) in the hard palate. A biopsy revealed verrucous tumor. Resection of the lesion with wide margins was performed. Grossly, the palate tumor was pedunculated and verrucous, but a depressed area (8 x 7 mm) was recognized. Microscopically, the verrucous ares showed verrucous proliferation of squamous epithelium with little cellular atypia, and was interpreted as VC without invasion. The depressed lesion was obvious SCC with invasion. There were direct transitions between the VC and SCC. Immunohistochemically, the VC and SCC tumor cells were negative for human papilloma virus antigens. P53 protein was expressed in both VC and SCC, though the expression in SCC was much more strong and broad than that in VC. The Ki-67 antigen was also expressed in the VC and SCC, and Ki-67 labeling index ranged was 12% in VC and 64% in SCC. These findings indicate that SCC may arise within VC.